(untitled) (Indian Journal of Public Health Research & Development, 2023)
Background: Malnutrition in children is global issue that may have both short- and long-term irreversible negative health consequences. Objectives: To determine the prevalence of under-nutrition among the under-five children inrural area of Haldwani. Material and methods: Community-based cross-sectional study. Results: Four-hundred children were examined. The prevalence of undernutrition among children was depicted as underweight, stunting and wasting was 7.75%, 9.25% and 4% respectivel